Dialogic pedagogy versus punitive approaches through school rules?: School practitioners’ perspectives in two schools in Yogyakarta, Indonesia - Nurwanto, Nurwanto; Makrufi, Anisa Dwi; Wiyono, Giri (Psychology, Evaluation, and Technology in Educational Research, 2024)
This article aims to investigate how dialogic pedagogy was practiced while punitive approaches were dominant towards students who violated school rules as well as the student code of conduct. Previous studies primarily focused on the extent of effectiveness or the influential factors for students to comply with as well as violate student code of conduct. On the other hand, this writing highlights the importance of dialogic practices in school environments. As a case study, this study investigated two senior high schools, that is the public and private schools in Yogyakarta municipality. Through the documentary and interview analysis, the study found that even if the student code of conduct was punitive approach-based, it contains the potential for school practitioners to develop communications or dialogues, for example, between school practitioners themselves; and between school practitioners (school leaders and educators) and parents; and between school practitioners and students. More importantly, several school leaders and educators emphasized how dialogues could be practiced with students considered as the offenders of the school rules. This article concludes that empathetic and critical dialogues seem to be an alternative of student discipline enforcement, which has been largely practiced through the school rules.